Profiles and Predictors of Functioning Among Adults in Recovery from Alcohol Use Disorders - Danielle Dick; Mary Loos; Vivia McCutcheon; Emma C. Johnson; Fazil Aliev; Thomas Bannard; Wendy Kliewer; Dace Svikis; Sarah Colbert; Rebecca L. Smith (OSF Registries, 2022)
The goal of this project is to elucidate the patterns, predictors, and processes of recovery from SUDs. In the proposed study, we will use a family-based, genetically informed dataset of adults that was enriched for risk of AUD, the Collaborative Study on the Genetics of Alcoholism (COGA) Prospective Study (N = 3,129). Based on the recent emphasis on understanding functioning and wellbeing among individuals beyond their remission status, we will characterize and predict patterns of functioning related to quality of life in a sample of individuals who reduce their symptoms such that they no longer meet AUD criteria. We will first investigate profiles of functioning related to quality of life among a sample of individuals in remission from AUD. Next, we will examine predicters of profile membership. We will test whether proximal sources of recovery capital (social support for recovery, attendance at religious services, treatment history) and distal sources of negative recovery capital (deviant peer affiliation during adolescence, interpersonal trauma) predict profile membership. We will also test the extent to which epidemiological risk factors (substance use history, internalizing and externalizing behaviors), and genetic liabilities towards alcohol problems, externalizing behaviors, and internalizing behaviors influence patterns of quality of life. Findings from this study will elucidate the role of a diversity of distal and proximal influences on patterns of quality of life, and may lead to an improved understanding of AUD recovery trajectories.
Keywords: Psychiatry and Psychology; Medicine and Health Sciences; Life Sciences; Mental and Social Health; Social and Behavioral Sciences; Psychology; Genetics and Genomics; addiction; alcohol use disorder; coga; quality of life; recovery; recovery science